Fifteen years of NaV1.7 channels as an analgesic target: Why has excellent in vitro pharmacology not translated into in vivo analgesic efficacy?. (18th December 2020) - Eagles, David A.; Chow, Chun Yuen; King, Glenn F.
Abstract : In 2006, humans with a congenital insensitivity to pain (CIP) were found to lack functional NaV 1.7 channels. In the subsequent 15 years there was a rush to develop selective inhibitors of NaV 1.7 channels with the goal of producing broadly effective analgesics without the problems of addiction and tolerance associated with opioids. Pharmacologically, this mission has been highly successful, leading to a number of highly potent and selective inhibitors of NaV 1.7 channels. However, there are very few examples where these inhibitors have yielded effective analgesia in preclinical pain models or human clinical trials. In this review, we summarise the role of the NaV 1.7 channel in nociception, its history as a therapeutic target and the quest to develop potent inhibitors of this channel. Finally, we discuss possible reasons why the pain‐free state seen in humans with CIP has been so difficult to replicate pharmacologically. LINKED ARTICLES: This article is part of a themed issue on Structure Guided Pharmacology of Membrane Proteins (BJP 75th Anniversary). To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v179.14/issuetoc